Digital Arbitration and Online Dispute Resolution in Indonesia: Regulatory Challenges, Technological Opportunities, and the Future of Arbitration Law - Irham Mahromy Munthe; Maria Arfah Nasution; Ahmad Yasin Dongoran; Usamah Zaki (Jurnal Cendikia ISNU SU, 2026)
This study examines the challenges and opportunities of arbitration in the digital era, focusing on the legal and practical perspectives of online dispute resolution in Indonesia. The research is motivated by the rapid development of information technology, which has transformed dispute resolution mechanisms through digital platforms, particularly in e-commerce transactions and cross-border contracts. This study employs a normative legal approach or doctrinal research, analyzing legislation, legal theory, academic literature, and jurisprudence related to digital arbitration. The research stages include problem identification, literature review, collection of primary and secondary data, and qualitative analysis to evaluate the challenges and benefits of digital arbitration. The findings indicate that while national regulations do not explicitly govern online arbitration, they provide a legal foundation through principles of party consent, arbitrator independence, and award recognition. Moreover, digital arbitration offers cost and time efficiency, procedural flexibility, broader access, and technological innovations, provided that fairness, confidentiality, and legal certainty are ensured through secure platforms and competent arbitrators. Unlike previous studies that primarily discuss the procedural legality of online arbitration, this article develops a broader analytical framework by examining the interaction between digital technology, procedural fairness, cybersecurity, and regulatory adaptation within Indonesia's arbitration regime. It argues that the future legitimacy of digital arbitration depends not merely on technological adoption but on the development of an integrated regulatory ecosystem capable of balancing efficiency, due process, confidentiality, and enforceability. Accordingly, this study contributes to contemporary arbitration scholarship by proposing a regulatory model for strengthening online dispute resolution in emerging digital economies.